Reviews - Gómez-Puertas, Lorena and Farré, Jordi and Sendra, Anna and Daries, Natalia (Catalan Journal of Communication & Cultural Studies, 2017)
Abstract MOTHERHOOD IN THE MEDIA. INFANTICIDE, JOURNALISM AND THE DIGITAL AGE, BARBARA BARNETT (2016) New York: Routledge, Series: Routledge Research in Cultural and Media Studies, 84, 224 pp., ISBN: 9781138889170, h/bk, ₤90.00, e/bk, ₤24.49 THE MEDIA SYNDROME, DAVID L. ALTHEIDE (2016) New York and London: Routledge, 233 pp., ISBN: 9781629581477, h/bk, ₤90.00, p/bk, ₤22.99 SOCIAL MEDIA IN MEDICINE, MARGARET S. CHISOLM (ED.) (2016) London and New York: Routledge, 96 pp., ISBN: 9781138665385, h/bk, ₤90.00 LA COMUNICACIÓN DE LOS DESTINOS TURÍSTICOS Y SUS MARCAS A TRAVÉS DE LOS MEDIOS SOCIALES, ASSUMPCIÓ HUERTAS (ED.) (2016) Tarragona: Universitat Rovira i Virgili, 93 pp., ISBN: 978-84-608-8771-3, ebk, free of charge
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9jamNzLjkuMS4xNjNfNQ